How do you factor 60(x^2-3) and also how do you factor (3x^5-20x^3)?? 3/8/2014 | Hunter from Fort Collins, CO | 3 Answers | 0 Votes Mark favorite Subscribe Comment
60(x^2-2) = 60(x^2-(√(2))^2) = 60(x+√(2))(x-√(2)) 3x^5 – 20x^3 = x^3(3x^2 – 20) = x^3((√(3)x)^2 – (2√(5))^2) = x^3(√(3)x + 2√(5))(√(3)x – 2√(5)) 3/8/2014 | Steve S. Comment Comments Good ! 3/8/2014 | Parviz F. Comment
60 ( X^2 -2) = 60 ( X + √2) ( X - √2 ) 3X^{5 }- 20 X^{3 } = X^{3 }(3X^{2} - 20 ) = X^{3 }( (√3) X +√20 ) ((√3) X - √20 ) 3/8/2014 | Parviz F. Comment
Hi Hunter; 60(x^{2}-2) This is factored. If you want to un-factor this... 60x^{2}-120 (3x^{5}-20x^{3}) x^{3}(3x^{2}-20) 3/8/2014 | Vivian L. Comment
Comments